ENSEÑANZA DE MÉTODOS NUMÉRICOS A TRAV ÉS DE UNA HERRAMIENTA DIDÁCTICA BASADA EN ARDUINO: EL MECANISMO DE LAS 4 BARRAS REVISITADO. - SERRANO-PÉREZY, E. (Revista Cubana de Física, 2021)
In this work, an educational tool for teaching numerical bisection and secant methods through its hardware implementation with an Arduino Due based card is presented. It is an accessible practice for the university level in which students who are not familiar with the programming languages can learn both numerical methods and the Arduino programming language due to its accessibility and simplicity. To verify results and as a means of debugging programs in the Arduino language, a spreadsheet is also used. As a case study, the classic problem of the 4-bar mechanism is revisited from a technological perspective, using a 32-bit microcontroller as a calculation tool. It is expected that development of traditional practices which are reviewed from a technological approach applied to real case studies, will encourage students to develop new prototypes and tangible technological developments by using the software and hardware tools to implement algorithms of numerical methods that solve complex engineering and physics problems.